Cardioaortic replacement for a ruptured root pseudoaneurysm with pulsatile subcutaneous extension. (4th January 2019) - Wang, Hanjay; Shudo, Yasuhiro; Hittinger, Scott A; Woo, Y Joseph
Abstract: Orthotopic heart transplantation with concomitant aortic surgery is rarely performed. Herein, we describe the successful management of a patient with an otherwise inoperable, ruptured aortic root pseudoaneurysm using combined cardioaortic replacement under hypothermic circulatory arrest.